Regional Experience in Organizing and Holding a Competition of Professional Skills “Teacher-Psychologist” in the Sverdlovsk Region - Vasyagina, N.N.; Shempeleva, N.I.; Bulatova, N.A. (Bulletin of Practical Psychology of Education, 2022)
The article is aimed at describing the professional skill contest “Teacher-Psychologist” as one of the effective mechanisms for stimulating and supporting the professional development of the personnel potential of the psychological service in the education of the Sverdlovsk region. The paper pays attention to the peculiarities of the organization and conduct of the competition in the region, considers changes in the content of competitive tests, which vary in accordance with modern trends in the development of psychological science and psychological and pedagogical services in the education system and the specifics of the region. The analysis of the eight-year experience of the Teacher-Psychologist competition in the Sverdlovsk region allows us to note positive trends in the change of motivation and the level of professional competence of teachers-psychologists, which are reflected in the high performance of specialists of the Sverdlovsk region at the federal stage of the competition. Of great importance in achieving such high results is the training of contestants in the region, which is organized in the form of teamwork involving participants and winners of the federal stage of the competition, and is conducted under the guidance of the Chief Freelance Psychologist of the Sverdlovsk region, which ensures the success of the presentation of professional skills by the contestants. В статье описывается конкурс профессионального мастерства «Педагог-психолог» как один из эффективных механизмов стимулирования и поддержки профессионального развития кадрового потенциала психологической службы в образовании Свердловской области. Также уделено внимание особенностям организации и проведения конкурса в регионе, рассматриваются изменения в содержании конкурсных испытаний, которые варьируются в соответствии с современными тенденциями развития психологической науки и психолого-педагогической службы в системе образования и со спецификой региона. Результаты анализа восьмилетнего опыта проведения конкурса «Педагог-психолог» в Свердловской области позволяют отметить позитивные тенденции в том, как меняется мотивация и уровень профессиональной компетентности педагогов-психологов. Данные изменения проявляются в высоких показателях специалистов Свердловской области на федеральном этапе конкурса. Большое значение в достижении таких высоких результатов имеет подготовка конкурсантов в регионе, которая организована в форме командной работы (с привлечением участников и победителей федерального этапа конкурса), и проводится под руководством главного внештатного психолога Свердловской области, — чем и обеспечивается успешность представления профессионального мастерства конкурсантами.